An interactive multi-objective optimization framework for sustainable design of bioprocesses - Taras, Sandu; Woinaroschy, Alexandru (Computers & chemical engineering, 2012)
► An interactive multiobjective optimization strategy of bioprocess is proposed. ► An optimization tool based on proposed methodology is created. ► The created tool is applied for optimization of an l-lysine feed supplement plant. ► The results obtained show the viability of the proposed strategy. ► We lay the foundation for development of a powerful optimization tools. Interactive multi-objective optimization methods have considerable advantages over the other multi-objective optimization methods and are well suited for biochemical engineering problems. Interactive optimization is a very complex task which requires appropriate software to handle multiple objectives, displaying intermediary results and allowing the decision maker to specify preferences for each iteration. The proposed strategy combines Matlab and SuperPro Designer simulator. This way, the SuperPro Designer simulator benefits from the available toolboxes, computation, and visualization advanced features of Matlab. By linking Matlab and SuperPro Designer simulator, an optimization loop is created. This allows an automatically and repeatedly bidirectional exchange of variables between optimization algorithm from Matlab and SuperPro Designer simulator. In order to fully automate the optimization process, software based on Component Object Module technology, which contains three friendly graphical interfaces, was created. The presented strategy is implemented for a l-lysine feed supplement plant, both economic and environmental objectives being considered.